AKTIVITAS INHIBISI ENZIM ALFA-GLUKOSIDASE DARI EKSTRAK KULIT BATANG BUNGA KUPU-KUPU (Bauhinia semibifida Roxb) SECARA IN VITRO - Haiyul Fadhli; Nofri Hendri Sandi; Ainun Nurain Nurdin (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Research on the activity of ?-glucosidase inhibition of Bunga Kupu-Kupu stem bark extract (Bauhinia semibifida Roxb) has been carried out in vitro. This study aims to determine the inhibitory activity of the extracts of B. semibifida Roxb. stem bark against the ?-glucosidase enzyme in vitro. Testing the inhibitory activity of the ?-glucosidase enzyme using extracts of n-hexane, ethyl acetate, and methanol from the stem bark of the Bunga Kupu-Kupu and the Akarbose as a positive control. In vitro testing was carried out using a microplate reader instrument with a wavelength of 410 nm. The results showed that the extract of n-hexane extract of the B. semibifida stem bark had an IC50 value 15,625 µg/mL, ethyl acetate extract had an IC50 value 35,495 µg/mL, and the methanol extract had an IC50 value 34,279 µg/mL. By category, the three B. semibifida stem bark extracts have the active ability to inhibit the ?-glucosidase enzyme, while the Akarbose had an IC50 value 0,384 µg/mL as a positive control has a very active ability as an antidiabetic through the inhibition of the ?-glucosidase enzyme. The results showed that extraction of ?-glucosidase inhibitor compound with n-hexane yielded extract with highest inhibitor activity.